The Lexico-Semantic Analysis of the Common and Various in World of Gender Picture in the English and Tatar Linguistic Cultures - Khuzina, Ekaterina; Mukhtarova, Rezeda (Journal of History Culture and Art Research, 2018)
Phraseological unit is a peculiar unit of language, as complex and contradictory as language and culture. The results of a contrastive description of phraseological units cast light on the general and the differing of conceptual metaphors, which predetermines the similarities and differences of linguistic world-images. The ways of reflecting the extralinguistic reality being different for each individual language are formed in linguistic world-images. As a result, each language view of the world is characterized by cultural concepts, attitudes, and stereotypes. The value world view is a part of the linguistic world-image, since the reasoning about the good and the evil is an integral part of any society, language and culture. The universal concepts such as person, man, woman are reflected in language, and every culture comprehends its own values that must be inherent in person, man, woman. What determines these values – what is good and what is bad? An obligatory component of evaluation which directs the movement of the value judgment along the estimation scale is value stereotypes and attitudes. Linguistics demonstrates how social stereotypes influence the perception of the words such as “woman”, “man”. Social stereotypes often provoke discussions and turn into acute problems with the democratization of society, for example, a good wife – the keeper of the hearth, the hostess in the house. This paper, by comparing Tatar and English languages, examines gender structure in phraseological units.